Apocalyptic Foreboding in Eliot’s Poetry: A Study in Dark Romanticism - Khan, Mujahid; Shaheen, Aamer; Qamar, Sadia (Annals of Human and Social Sciences, 2023)
T.S. Eliot’s poetical writings disclose a strong inclination towards Dark Romanticism, a sub-genre that emerged from the traditional romantic ideals of Romanticism. He acknowledges human imperfections and sees nature as oppressive, echoed in his poetry filled with ‘dark themes,’ ‘bleak images,’ and a sense of ‘isolation and despair.’ Eliot critiques society’s values and reflects its ‘immorality,’ ‘darkness,’ and ‘ugliness,’ akin to Dark Romantics. His verses explore the darker aspects of spiritual truth, the human soul, and the natural world, portraying a world shrouded in ‘darkness,’ ‘despair,’ and ‘looming doom.’ This paper examines how Gothic and Dark Romantic elements in his poetical works mirror the anxieties of a society on the brink of self-destruction, arguing that Eliot’s use of themes like ‘decay’ and ‘desolation’ effectively foreshadow the anxieties of modern society and its potential for self-ruin.